Structures of Organisation and Loci of Authority in a Glocal Islamic Movement: The Tablighi Jama'at in Britain - Timol, Riyaz (Religions, 2019)
The Tablighi Jama'at (TJ) is widely regarded as the largest grassroots Islamic revival movement in the world, but it remains significantly under-researched. This paper, based on sustained ethnographic fieldwork conducted between 2013 and 2015, provides a comprehensive overview of the movement's organisational structures and loci of authority in Britain. It describes how different levels of the movement interact, from the local and regional to the national and international, to constitute a truly glocal movement. TJ's European headquarters, located in Dewsbury, West Yorkshire, is identified as a centralised hub that for several decades has co-ordinated the movement's activities in the West through the devoted leadership of Hafiz Muhammad Patel (1926-2016) and ongoing contact with the global spiritual centre in Nizamuddin, New Delhi. TJ's simultaneous links with hundreds of mosques across the country, largely—though not exclusively—of Deobandi orientation, are also described. The functioning of its regional centres of operation in Birmingham, Blackburn, Glasgow, Leicester and London is elaborated with reference to key weekly meetings convened on-site and the "routing" of numerous TJ groups to various British mosques each weekend. Although TJ's leadership has recently become embroiled in schism, the paper argues for the successful establishment of a robust institutional infrastructure in Britain which has facilitated the movement's transmission to a generation of British-born activists.